Oxygen-Enhanced 3D Radial Ultrashort Echo Time Magnetic Resonance Imaging in the Healthy Human Lung - Kruger, Stanley J (NMR Biomed, 2014)
PURPOSE: To use 3D radial ultrashort echo time MRI to perform whole-lung oxygen-enhanced (OE) imaging in humans. METHODS: Eight healthy human subjects underwent two 3D radial UTE MRI acquisitions (TE = 0.08 ms): one while breathing 21% O(2) and the other while breathing 100% O(2). Scans were each performed over 5 minutes of free breathing, using prospective respiratory gating. For comparison purposes, conventional echo time (TE = 2.1 ms) images were acquired simultaneously during each acquisition using a radial “outward-inward” k-space trajectory. 3D percent OE maps were generated from these images. RESULTS: 3D OE maps showing lung signal enhancement were generated successfully in seven subjects (technical failure in one subject). Mean percent signal enhancement was 6.6% ± 1.8%, near the value predicted by theory of 6.3%. No significant enhancement was seen using the conventional echo time data, confirming the importance of UTE for this acquisition strategy. CONCLUSION: 3D radial UTE MRI shows promise as a method for OE MRI that enables whole-lung coverage and isotropic spatial resolution, in comparison to existing 2D OE methods that rely on a less time-efficient inversion recovery pulse sequence. These qualities may help OE MRI become a viable low-cost method for 3D imaging of lung function in human subjects.